2004
DOI: 10.4049/jimmunol.173.2.1118
|View full text |Cite
|
Sign up to set email alerts
|

A Short Consensus Repeat-Containing Complement Regulatory Protein of Lamprey That Participates in Cleavage of Lamprey Complement 3

Abstract: The prototype of the short consensus repeat (SCR)-containing C regulatory protein is of interest in view of its evolutionary significance with regard to the origin of the C regulatory system. Lamprey is an agnathan fish that belongs to the lowest class of vertebrates. Because it does not possess lymphocytes, it lacks Ig and consequently the classical C pathway. We identified an SCR-containing C regulatory protein from the lamprey. The primary structure predicted from the cDNA sequence showed that this is a sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…7A). The amounts of bound proteins were compared with that of lamprey complement 3 (AY359861) (20), which do not bind GST-FlaA. The binding assay suggested that rtTLR5S has sufficient affinity to hold flagellin.…”
Section: Identification Of Tlr5-like Sequences From the Rainbowmentioning
confidence: 99%
“…7A). The amounts of bound proteins were compared with that of lamprey complement 3 (AY359861) (20), which do not bind GST-FlaA. The binding assay suggested that rtTLR5S has sufficient affinity to hold flagellin.…”
Section: Identification Of Tlr5-like Sequences From the Rainbowmentioning
confidence: 99%
“…As for function of RCA in the lower vertebrates, regulatory roles in deposition of C3 and degradation of C3b/C4b have been described only for secreted RCAs in lamprey (35) and barred sand bass (28)(29)(30). No functional data, in contrast, have been reported for membrane-bound RCA protein in any lower vertebrate species.…”
mentioning
confidence: 95%
“…Calcein release cytotoxicity test was performed, as described elsewhere (35). Briefly, transfected CHO cells (1.0 3 10 4 cells) were seeded in each well of 96-well plates and cultured overnight at 37˚C in 5% CO 2 .…”
Section: Calcein Release Assay For Complement-mediated Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by expressing specific domains: short consensus repeat (SCR) or control unit complement proteins (CCP). [11,14,15] Factor H contains 20 of these domains (see Figure 2). Figure 2.…”
Section: The Cfh Gene Is Located In the Long Arm Of Chromosomementioning
confidence: 99%